Modified early warning score predicts the need for hospital admission and inhospital mortality. Issue 10 (8th October 2008) - Burch, V C; Tarr, G; Morroni, C
Abstract : Background: The modified early warning score (MEWS) is a useful tool for identifying hospitalised patients in need of a higher level of care and those at risk of inhospital death. Use of the MEWS as a triage tool to identify patients needing hospital admission and those at increased risk of inhospital death has been evaluated only to a limited extent. Aim: To evaluate the use of the MEWS as a triage tool to identify medical patients presenting to the emergency department who require admission to hospital and are at increased risk of inhospital death. Methods: Physiological parameters were collected from 790 medical patients presenting to the emergency department of a public hospital in Cape Town, South Africa. MEW scores were calculated from the data and multivariate regression analysis was performed to identify independent predictors of hospital admission and inhospital mortality. Results: The proportion of patients admitted and those who died in hospital increased significantly as the MEW score increased (p<0.001). Multivariate regression analysis identified five independent predictors of hospital admission: systolic blood pressure ⩽100 mm Hg, pulse rate ⩾130 beats per minute, respiratory rate ⩾30 breaths per minute, temperature ⩾38.5°C and an impaired level of consciousness. Independent predictors of inhospital death were: abnormal systolic blood pressure (⩽100 or ⩾200 mm Hg), respiratory rate ⩾30 breaths per minute and an impaired level of consciousness. Conclusion: The MEWS, specifically five selected parameters, may be used as a rapid, simple triage method to identify medical patients in need of hospital admission and those at increased risk of inhospital death.